The burdens of primitive communism - Grant, Bruce (Anuário Antropológico, 2018)
Gilyaks (Nivkhi, by Russian twentieth century nomenclature) are famous for their indigenism. Like Maasai, Nuer, Trobrianders and Yanomami, they became famous in the ethnographic literature of their country as models for theory, ideology and method - foils for an understanding of the world at large. But such frame brings a price. Relative to their work elsewhere, the Soviet government invested disproportionately extensive resources in programs designed to modernize and re-educate their high profile Gilyak subjects. In this article, I track how 5000 Gilyak fishers and hunters on imperial Russia’s far eastern shores became seen as the early USSR’s “truest proletarians” in the eyes of their most famous anthropologist, Lev Shtemberg. A striking illustration of the fortunes of political ideology, Shtemberg’s life and work illustrates how early Marxist kinship studies took a Pacific people and made them a hallmark of primitive communist life in the Russian imperial imagination. In turn, Nivkhi of the late 20th century reflect back today on the political burdens of having been among the foremost subjects o f Soviet ethnographic literature.